Culture and ELT: Cambodian teachers' perception and practice of textbook adaptation to realize intercultural awareness - Nhem, Davut (ELT Forum: Journal of English Language Teaching, 2020)
Currently, it is recognized that language and culture go hand in hand, which means that when we teach a language, we also teach the culture of that language or other languages that appear in the textbooks being used. This wide recognition of the vital role of culture in the second language teaching has presented challenges for EFL teachers in various contexts. This article reports a qualitative study on three Cambodian teachers of English at one school in Phnom Penh. The study aims to investigate EFL teachers’ views and practices of textbook adaptation, as well as how they adapt textbooks to help students develop intercultural awareness in the ELT. To achieve these objectives, the qualitative data obtained from individual interviews, classroom observations, and teaching materials were engaged to shed light on the backdrop of the textbook adaptation and cultural integration in the ELT classroom. The findings in this study reveal an inconsistency between teachers’ views and practices about the textbook adaptation and the teachers’ limited capacity of interculturality-stimulated scholarship that is inherently tied to the development of cultural activities in the ELT classroom. This study suggests teacher training on the textbook adaptation and teaching culture should be provided to the teachers in the context and beyond.